(untitled) (Penang, 2017)
SEAMEO RECSAM with its mandate to promote science and mathematics in the Southeast Asian region, led one of the 12 initiatives known as SEAMEO Basic Education Standards (SEA-BES) and Student Networking, which later became two separate projects. The SEA-BES project came into life in November 2014 through a regional consultative meeting back to back with the Southeast Asia Primary Learning Metrics (SEA-PLM) project with funding from UNICEF East Asia Pacific Regional Office (UNICEF EAPRO).
Keywords: Toán học,Mathematics,Khoa học,Science; Dạy và học,Study and teaching,Dạy và học,Study and teaching